Analisis Peran Transpor Membran dalam Respons Stres Abiotik: Implikasi pada Pertumbuhan dan Perkembangan Tanaman - Dian Dwi Lestari; Nia Febrianti; Adnan (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
Abiotic stress is an environmental condition that is unfavorable for plants such as drought, salinity, heavy metal contamination and nutrient deficiencies. Prolonged abiotic stress causes the stability of plant cell organelles to be disrupted, thereby inhibiting plant growth and development. This research aims to examine the role of membrane transport in responding to environmental stress, especially abiotic stress, and the implications for plant growth and development. The research method used was a literature study using meta-analysis techniques assisted by prism diagrams in analyzing 14 relevant scientific articles from various national and international journals. The analysis was carried out descriptively on the results of previous research. The results show membrane transport has a role in increasing plant resistance to abiotic stress. Cell membrane structure consisting of lipids, proteins and carbohydrates has been proven to increase plant safety from environmental stress. So it can be concluded that membrane transport has a role in mediating tolerance, resistance, and resolving plant stress conditions through maintaining cellular homeostasis. Implications of this research can help expand knowledge about how plants respond to unfavorable environmental conditions through membrane transport mechanisms and can be basis for developing plant varieties are resistant to various forms of environmental abiotic stress.